Analisis Stabilitas Lereng Bendungan 1 Tujuh Bukit Tumpang Pitu Banyuwangi - Widde Valensia; Yanyan Agustian (Jurnal Ilmiah Teknologi Infomasi Terapan, 2024)
The operational success of a dam is significantly influenced by slope stability and seepage safety. This study aims to evaluate the slope stability and seepage safety of the Tujuh Bukit 1 Dam, which has been in operation for five years. The research methodology involves the collection of both primary and secondary data, followed by the development of analysis models. The slope stability analysis was conducted under three conditions: static, Operated Based Earthquake (OBE), and Maximum Design Earthquake (MDE). Additionally, a seepage analysis model was developed to assess safety against uplift pressure and piping erosion. The results indicate that slope stability under static, OBE, and MDE conditions meets the required safety criteria. The factors of safety calculated for each scenario demonstrate that the dam slopes are stable and capable of withstanding the specified loads. Similarly, the seepage analysis results show that the Tujuh Bukit 1 Dam is safe against both uplift and piping erosion, with no significant risk of internal erosion or material loss that could compromise the structure. Based on these analysis results, no additional design modifications or reinforcements are required for the Tujuh Bukit 1 Dam. The current design and construction are adequate to ensure the dam's safety and stability under the evaluated conditions. These findings provide confidence in the dam's operational reliability and valuable insights for future monitoring and maintenance strategies. This study underscores the importance of regular safety evaluations for dams and highlights the effectiveness of detailed analytical models in assessing stability and seepage concerns Keywords: Slope Stability, Seepage Safety, Tujuh Bukit 1 Dam